Case report: 5-year progression free survival and complete liver response in a patient with metastatic breast cancer treated with everolimus plus exemestane. Issue 31 (31st July 2020) - Krasniqi, Eriseld; Barchiesi, Giacomo; Mazzotta, Marco; Pizzuti, Laura; Villa, Alice; Barba, Maddalena; Vici, Patrizia
Abstract: Rationale: Within a rapidly expanding therapeutic armamentarium, the combination of everolimus (Eve) plus exemestane (Exe) utility needs to be reinstated in hormone receptor positive (HR+), human epidermal growth factor receptor 2 negative (HER2–) metastatic breast cancer (MBC). Patient concerns: We herein report on a patient affected by HR+ HER2– MBC treated with radical surgery after neoadjuvant chemotherapy, who relapsed early on adjuvant tamoxifen, progressed rapidly on first line anastrozole, and failed treatment with third line capecitabine. Diagnoses: Metastatic luminal breast cancer progressed under standard endocrine therapy and chemotherapy. Interventions: Third line with Eve plus Exe was given after chemotherapy. Outcomes: Patient experienced a 5-year progression free interval. Lessons: Eve plus Exe remains a valid option in HR+HER2– MBC.